Assessing immuno-expression of p53 protein and TP 53 gene amplification in histologically negative surgical margins of oral squamous cell carcinoma patients and normal oral mucosa - Kamat, Mamata S.; Puranik, Rudrayya S.; Das Rai, A. Bhagavan; Patil, B. R.; Patil, Shankargouda (Clinical oral investigations, 2022)
Objective To assess and compare the immuno-expression of p53 and TP 53 gene amplification and correlate local recurrence and survival in histologically negative surgical margins of oral squamous cell carcinoma (OSCC) with normal oral mucosa. Methods Forty formalin-fixed paraffin-embedded tissue blocks of HNMs of OSCC and 40 normal oral mucosa samples were analyzed for p53 immunostaining and TP 53 gene amplification by PCR. Results Significantly, higher positivity was noted with p53 immuno-expression, TP53 gene amplification, and combined p53 and TP53 expression in the study group compared to the control group ( p < 0.05). Most cases that were positive for p53 immuno-expression, TP 53 gene amplification, and combined p53 and TP53 expression showed local recurrence and poor survival. Kaplan–Meier survival analysis showed that subjects with TP53 and combined p53 and TP53 positivity had decreased survival rate than their negative counterparts. Conclusion Detection of p53 in HNMs of OSCC can be used as a biomarker to identify patients at a higher risk of developing local recurrence and to predict survival. Clinical relevance Combined p53 and TP 53 assessment may be more reliable for predicting LR to help clinicians and surgeons in treatment planning.